BUDAYA LISAN VS BUDAYA LITERASI MAHASISWA MELAYU: Implikasinya pada Model Pembelajaran Mahasiswa - Agus Syahrani (Jurnal Elektronik WACANA ETNIK, 2013)
This study reflects on complaints that some students have not been able to fulfill their duties and responsibilities to the fullest , especially in fulfilling the tasks of reading and writing . It is assumed to be closely related to the habits of the students related to deep-rooted social and cultural backgrounds of students are predominantly Malay cultural background with kelisanannya identity . Referring to the reality and mind, this study aims to reveal the habits of students in terms of orality and literacy , both as a duty to meet the needs of students as well as for other purposes such as for leisure . The data collection technique used is the technique of direct observation by researchers , discussion through Focused Group Discussion ( FGD ) and observation indirectly through questionnaires and equipped with library research . Qualitative data obtained from each instrument were analyzed and described qualitatively .